Resistance and Reinscription: Revitalizing Mi'kmaq Culture in Newfoundland - A Grounded Theory Discursive Analysis of Oppression and Resistance - Butler, Charles WIlliam James (Graduate Studies, 2014)
This dissertation utilizes a grounded theory methodology to explore the intersection between Indigenous and multi-cultural societies. It focusses on an Indigenous people who have long been framed as fully assimilated into white society. It critiques how Canada purports to be a multi-cultural mosaic in a post-colonial state and argues that these concepts fail to account for the presence of Indigenous peoples, their interactions with the dominant settler society and the fact that the Indian Act represents the ongoing colonization of Indigenous people. Further, it argues that discussions of the place of Indigenous people in Canada often work from the assumption that in order to survive and to prosper, Indigenous people must abandon many of the key cultural practices that differentiate their worldview from that of the settlers. That is, they must choose to be assimilated and to become hyphenated-Canadians. This thesis examines how Mi’kmaq in Newfoundland are revitalizing their Indigenous culture through resistance and reinscription. It problematizes notions of hybridity and challenges the authority of governments, which seek to control Indigenous identity through a legislative framework, oppression, and marginalization. It argues for the legitimacy and authenticity of Indigenous identities that incorporate cultural practices from Pan-Indian sources in order to re-establish holistic Indigenous cultures. Finally, it presents an alternative understanding of how Indigenous identities can continue to flourish even when immersed in a society, which seeks to erase them.